Citizenship Education-Based Children's Character Development - Adelina Br. Sembiring; Defi Antika; Siti Amsarina Pangaribuan; Trisna Pratiwi Hasibuan (Yayasan Zia Salsabila, 2022)
In order to achieve bright and good children, it is important for teachers, parents and community members to make an impact on students' education. This study aims to describe the paradigm of civic education in this regard. With the help of literature study methods, this research takes a qualitative approach. The purpose of the study and data analysis is carried out by studying various relevant journals and other publications related to the problem to be solved. To find out more about previous researchers who have studied the same problem or the subject of current conversation. For this reason, data validation in this study was carried out by utilizing the main reference sources. Based on this research, it is hoped that teachers can apply methods or ways of teaching that can improve character and change children's mindsets such as applying the Pancasila precepts in everyday life in order to produce smart and good students.